El uso de las transferencias privadas inter-vivos por los hogares: el caso de México - Mayer Foulkes, David; Le Thi, Mai Lihn (El Colegio de México A.C., 2008)
Studies on how private inter-vivos transfers are spent are relatively scarce. This article compares the marginal tendency to spend on different items (including health and education) of households that receive private transfers, compared with those that do not. On the basis of information drawn from the Ennvih 2002 survey, the article concludes that marginal spending on children’s food, health and education is greater in households that receive some type of transfer than in those that do not. This pattern of consumption is mainly due to their specific characteristics, rather than to the transfers themselves.